Analysis and generalization of competitive activity results of handball clubs in the game development aspect - O. M. Solovey; O.O. Mitova; D.O. Solovey; V.V. Boguslavskyi; O.M. Ivchenko (IP Iermakov S.S., 2020)
Purpose: an analysis of the competitive activity of men's club handball teams in the final tournament of the European Champions and Champions League Cup gives you the opportunity to determine the rating of the teams on the continent and the development tendencies of the game. Material: the best men's handball clubs from 52 national federations in Europe which competed in the qualifying tournament and the group stages of the draw and were the winners and prize winners of the European Champions and Champions League Cup of 1956/1957-2017/2018. A systematic review of the available qualitative literature was conducted according to Preferred Reporting Items for Systematic reviews. The "Web of Science", "Physical Education Index (ProQuest)", "Google Scholar" and "Scientific Periodicals Ukraine" databases were used in order to ensure, from an early stage, the scientific quality of the revised studies. The research was conducted based on 'any field' (e.g. title, abstract, text) and no restrictions were made regarding the language of publication. The terms used in the research were "teams scoring performance", "elite handball", "game location", "players exclusions", "home advantage", "quality", "opposition", and "indicators". The quality of the articles was assessed by a set of criteria developed by members of the Evidence for Policy and Practice Information and other specialists. The initial search found 132 journal articles; for a final list of 52 publications. Results: The article covers the organizational aspects of the competitive activity of men's handball clubs in Europe at the European Champions and Champions League tournaments from 1956 to 2018. The given analysis of the highest achievements of the leading handball clubs which are not only winners and prize winners, but also the countries that they represented. The winners and prize winners are marked both between teams of different countries and teams of one country. Conclusions: Achievements and rankings of the leading handball clubs in the international arena are the main components of preparing them for official competitions: new approaches to planning the preparation of players and teams for higher sports achievements and maximum realization of individual opportunities; the integration of the individual readiness of highly skilled handball players into leading handball clubs; to the important aspects of the new rules of the game, which are developed in the theory and implemented in practice; the main tendencies in the international and European handball that systematically develop and apply to a core of players as well as the next reserve.